1993
DOI: 10.1590/s0036-46651993000200014
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi meningoencephalitis and myocarditis in a patient with acquired immunodeficiency syndrome

Abstract: We report the case of a 52-year-old male heterosexual patient with acquired immunodeficiency syndrome (AIDS) and reactivation of Chagas' disease manifested by meningoencephalitis and myocarditis, diagnosed post-mortem. Unexplained reactivation of Chagas' disease should be included among the diagnostic criteria of AIDS in human immunodeficiency virus positive patients. On the other hand, AIDS should be considered in the differential diagnosis of patients with unexplained reactivation of Chagas' disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 10 publications
0
12
0
5
Order By: Relevance
“…In relation to the clinical focus of each organ affected, this was nonspecific, ranging to the central nervous system from headache, signs of intracranial hypertension, seizures, motor location and coma, generating diagnostic confusion, mainly with toxoplasmosis and tumors of the central nervous system 37,65,66,75,84 . For the heart, it consists of triggering or exacerbating congestive heart failure, arrhythmias, atrioventricular, heart and fascicular blocks 22,27,34,42 . The fact that the clinical picture presented in the reactivation in the heart, usually occurred in the natural evolution of the chronic chagasic cardiopathy 88,102 making the diagnosis difficult, unlike the central nervous system which does not present exuberant symptomatology in the chronic phase of the disease.…”
Section: Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…In relation to the clinical focus of each organ affected, this was nonspecific, ranging to the central nervous system from headache, signs of intracranial hypertension, seizures, motor location and coma, generating diagnostic confusion, mainly with toxoplasmosis and tumors of the central nervous system 37,65,66,75,84 . For the heart, it consists of triggering or exacerbating congestive heart failure, arrhythmias, atrioventricular, heart and fascicular blocks 22,27,34,42 . The fact that the clinical picture presented in the reactivation in the heart, usually occurred in the natural evolution of the chronic chagasic cardiopathy 88,102 making the diagnosis difficult, unlike the central nervous system which does not present exuberant symptomatology in the chronic phase of the disease.…”
Section: Casesmentioning
confidence: 99%
“…The clinical condition is nonspecific for including reactions from the acute phase: fever, poor general condition, disorientation, hepatosplenomegaly, lymphadenopathy, among others 22,23,32,42,81,93 . Specifically, the clinical condition refers to the place of the reactivation.…”
Section: Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients at especially high risk are those submitted for transplants [5,6], those that have leukemia [2], lymphoma [7], and especially, AIDS [3,4,[8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Myocarditis may occur associated with the CNS picture, or rarely as the sole manifestation [1,8,9,22]. A literature review showed CNS disease in 75% and cardiac involvement in 44% of cases [10].…”
Section: Discussionmentioning
confidence: 99%